2017
DOI: 10.1093/trstmh/trx009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the 2014/2015 Ebola outbreak on reproductive health services in a rural district of Guinea: an ecological study

Abstract: BackgroundThe 2014/2015 Ebola outbreak was the most sustained in history. In Guinea, we compared trends in family planning, antenatal care, and institutional deliveries over the period before, during and after the outbreak.MethodsWe carried out an ecological study involving all the health facilities during pre-Ebola (1 March 2013 to 28 February 2014), intra-Ebola (1 March 2014 to 28 February 2015) and post-Ebola (1 March to 31 July 2016) periods in Macenta district.ResultsUtilization of family planning decline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
120
1
6

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(138 citation statements)
references
References 18 publications
11
120
1
6
Order By: Relevance
“…It would be valuable to track how long it will take for the utilization of essential SRH services to return to their pre-outbreak levels once COVID-19 has become largely controlled. There is evidence that during the 2014-2015 Ebola outbreak in West Africa the utilization of family planning, antenatal care and institutional deliveries declined and did not fully recover to pre-outbreak levels for 6 months [17,18].…”
mentioning
confidence: 99%
“…It would be valuable to track how long it will take for the utilization of essential SRH services to return to their pre-outbreak levels once COVID-19 has become largely controlled. There is evidence that during the 2014-2015 Ebola outbreak in West Africa the utilization of family planning, antenatal care and institutional deliveries declined and did not fully recover to pre-outbreak levels for 6 months [17,18].…”
mentioning
confidence: 99%
“…[22][23][24] These impacts can persist long after the disease outbreak is contained. 25 However, much of the evidence available about these impacts on maternal and newborn health is either modelled or is from studies using secondary data such as population-based surveys and routine health management information system analysis. 22,26,27 Additionally, large disruption to health-seeking behaviour and healthcare provision is caused by the unprecedented measures countries implement to contain the pandemic (e.g., lockdowns, curfews, restrictions on public transport).…”
Section: Introductionmentioning
confidence: 99%
“…T he West African Ebola outbreak of 2013-2016 caused over 11,000 deaths (World Health Organization 2016a) and devastated the already fragile health systems of Liberia, Sierra Leone, and Guinea. During the crisis, staffing shortages, quarantines, interruptions to supply chain, health facility closures, and fear of health facilities and workers resulted in significant disruptions to the provision and utilization of a range of health services, including inpatient health services and surgery (Bolkan et al 2014), malaria treatment (Plucinski et al 2015), vaccinations (Barden-O'Fallon et al 2015), obstetric care (Barden-O'Fallon et al 2015;UNWomen 2014), and family planning (Barden-O'Fallon et al 2015;UNWomen 2014;Camara et al 2017).…”
mentioning
confidence: 99%
“…rollbacks in recent advances in contraceptive use and maternal and child health. A study of the impact of Ebola on reproductive health care in one district in Guinea found a 50 percent decline in family planning visits during the height of the crisis (Camara et al 2017). Prior to the crisis, Liberia and Sierra Leone had seen gains in expanding contraceptive prevalence, rising from 12 to 21 percent of all women in Liberia between (Liberia Institute of Statistics and Geo-Information Services 2008 and 8 to 21 percent in Sierra Leone between 2008(Statistics Sierra Leone 2009.…”
mentioning
confidence: 99%